Pseudo-MS3 Approach Using Electrospray Mass Spectrometry (ESI-MS/MS) to Characterize Certain (2E)-2-[3-(1H-Imidazol-1-yl)-1-phenylpropylidene]hydrazinecarboxamide Derivatives - Ali S. Abdelhameed; Adnan A. Kadi; Mohamed I. Attia; Rihab F. Angawi; Mohamed W. Attwa; Hany W. Darwish (Journal of Chemistry)
An approach for the use of in-source fragmentation with electrospray ionization followed by product ion scan in a triple quadrupole mass spectrometer system is described. This approach is based on the elucidation of the various fragmentation pathways by further dissociation of each fragment ion in the ion spectrum. This can be achieved predominately, by combining fragmentor voltage induced dissociation (in-source fragmentation) with subsequent collision-induced dissociation; this process can be referred to as pseudo-MS3 scan mode. This technique permitted unambiguous assignment and provided sufficient sensitivity and specificity. It is advantageous for structure elucidation of unknown compounds. We investigate the possibility of using in-source fragmentation with the diverse novel chemical entities encompassing different substituents. This process was intended to improve the qualitative capability of tandem mass spectrometry simulating the MS3 of ion trap for studying fragmentation mechanisms. The approach is to implement the investigated technique as a well established tool for the characterization of new pharmacologically important chemical entities. The data presented in this paper provided useful information on the effect of different substituents on the ionization/fragmentation processes and can be used in the characterization of (2E)-2-[3-(1H-imidazol-1-yl)-1-phenylpropylidene]-hydrazinecarboxamide derivatives 3a–h.